Illizi city sand impact on the output of a conventional solar still - Djamel Khamaia; Ridha Boudhiaf; Abderrahmane Khechekhouche; Zied Driss (ASEAN Journal of Science and Engineering, 2022)
Lack of drinking water is a global problem and especially in overdeveloped countries. this is why many research laboratories are focused on solving this problem. one of the simplest, economical, and environmental methods is the use of conventional solar stills. Sand from the city of Illizi in southern Algeria was used in our research to see how it affected solar distillation. So, with a dimension of (0.50 x 0.50 m), two identical solar stills were evaluated, one as a solar still reference (SSR) and the other as a solar still modified (SSM). The SSM contains sand. The findings reveal that there is no discernible difference in performance and that the improvement rate is extremely low, at 0.67 %.